2005
DOI: 10.1128/jvi.79.6.3675-3683.2005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cytomegalovirus Infection Leads to Significant Changes in the Composition of the CD8+T-Cell Repertoire, Which May Be the Basis for an Imbalance in the Cytokine Production Profile in Elderly Persons

Abstract: In spite of the present belief that latent cytomegalovirus (CMV) infection drives CD8؉ T-cell differentiation and induces premature immune senescence, no systematic studies have so far been performed to compare phenotypical and functional changes in the CD8 ؉ T-cell repertoire in CMV-infected and noninfected persons of different age groups. In the present study, number, cytokine production, and growth potential of naïve (CD45RA ؉ CD28 ؉ ), memory (CD45RA ؊ CD28 ؉ ), and effector (CD45RA؉ T cells were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
274
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 322 publications
(300 citation statements)
references
References 41 publications
18
274
1
7
Order By: Relevance
“…Although the TCR usage of these responses was not studied, we envisage considerable focusing because CMV-specific CD8 T cells are usually manifest as massive clonal expansions (17). Combined with other studies (43)(44)(45) this has led to a revised view of the consequences of long-term CMV carriage for the immunocompetent host.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TCR usage of these responses was not studied, we envisage considerable focusing because CMV-specific CD8 T cells are usually manifest as massive clonal expansions (17). Combined with other studies (43)(44)(45) this has led to a revised view of the consequences of long-term CMV carriage for the immunocompetent host.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ effector cell accumulation and in young individuals, who characteristically have high numbers of naive CD8 ϩ T cells and low memory/effector counts (15).…”
Section: Cd25mentioning
confidence: 99%
“…1B). CD25 mRNA analysis was performed using PCR and CD25-specific primers (15). Surface phenotype analysis of CD25 ϩ and CD25 Ϫ CD8 ϩ T cells by four-color flow cytometric analysis additionally revealed that both subpopulations were Ag-experienced T cells, because they expressed CD45RO, CD44 high , and CD95 (Fig.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…112 In the elderly, such CMVspecific T cells can comprise up to 15% of the total blood T-cell population. 113 We demonstrated that patients who are seropositive for CMV and who have CLL have increased relative and absolute numbers of CD8 ϩ T cells with this phenotype relative to that of age-matched control subjects. 114 This was independent of any evidence for active viremia.…”
Section: Improving T-cell Function and Activationmentioning
confidence: 99%